2010
DOI: 10.1038/hr.2010.25
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on arterial stiffness

Abstract: A systematic literature review was conducted using PubMed, Embase and the Cochrane Library to determine the effect of acute, chronic and passive smoking on arterial stiffness and to determine whether these effects are reversible after smoking cessation. A total of 39 relevant studies were identified and included. Acute smoking was found to cause an acute increase in arterial stiffness. Similarly, passive smoking increased arterial stiffness acutely and chronically. The majority of studies identified chronic sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
128
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 142 publications
9
128
2
1
Order By: Relevance
“…In contrast, from data previously reported [ 28 ], we observed a trend toward a decrease of dAix after smoking. However, because heart rate has been shown to be a possible confounder in the determination of dAix, no effect was observed after normalization for heart rate (dAix@75) [ 29 ].…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast, from data previously reported [ 28 ], we observed a trend toward a decrease of dAix after smoking. However, because heart rate has been shown to be a possible confounder in the determination of dAix, no effect was observed after normalization for heart rate (dAix@75) [ 29 ].…”
Section: Discussioncontrasting
confidence: 56%
“…26,27 Currently, the most popular method for evaluating arterial stiffness is obtained by estimating the pulse transit time between the carotid and femoral arteries using the tonometric technique. 8,19 This technique gives a reliable index of the regional AoStiff, 28,29 but represents only an estimate of the local AoStiff because it is a summation of the individual biomechanical properties of different arterial walls (that is, carotid, aorta, iliac and femoral arteries) located between the two recording sites. 30,31 Our data showed that IWV measurements are highly correlated with the carotid-femoral PWV, indicating that IWV also provides a reliable estimate of the regional AoStiff (see Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…The association between the CAVI and the progression of diabetes mellitus, another wellknown condition that contributes to vascular stiffness, has also been extensively studied 4,5) , and diabetes is an independent determinant of the CAVI values in hypertensive patients 16) . Smoking has been found to be a risk factor for increasing arterial stiffness 17) . One study noted that smoking causes a significant increase in arterial stiffness as measured by the CAVI and that the CAVI correlates with the Brinkman index, which suggests that the CAVI is a useful index of the degree of arterial stiffness caused by smoking 18) .…”
Section: Resultsmentioning
confidence: 99%